An acoustic structure design supported by shear thickening fluid for sound absorption - Aslan, Ramazan; Turan, Osman (Elsevier Ltd, 2021)
In this study, an acoustic structure consisting of cellular and perforated panel absorbers has been designed to noise control. Then, the sound absorption behaviour of designed acoustic structure has been investigated experimentally by reinforcing with STFs having different rheological properties. In addition, the sound absorption performance of the designed acoustic structure has been compared with the Gyroid which is a type of cellular sound absorber. The findings have indicated that the perforated panel activates significantly the sound absorption performance of the designed acoustic structure especially in the low (f[removed]3500Hz) frequency ranges. In addition, it has been also observed that this effect becomes stronger with STF reinforcement and significantly improves the sound absorption behaviour of the designed acoustic structure. Besides, it has been noticed that the sound absorption performance of the designed acoustic structure increases with increasing molecular weight of PEG for low frequencies (i.e. f[removed]3500Hz). Finally, it has been detected that the effectiveness of STF on the sound absorption performance of designed acoustics structure improves remarkably with increasing silica-nanoparticle ratio in the case of low and high frequencies (i.e. f[removed]3500Hz).
Keywords: 3d printing; Acoustic structure; Noise control; Shear-thickening fluid; Sound absorber